Определение оптимального расположения электродов пьезопривода форсунки - Стрелец, А.А. (Електротехніка і електромеханіка, 2011)
A problem of optimal electrode arrangement on a piezoelectric actuator under meeting conditions of the piezoelectric actuator maximum shift and shift control ability is considered in the article. With the help of experimental research, optimal arrangement of input and output electrodes on the surface of the piezoelectric actuator piezoelectric elements is specified.